1957
DOI: 10.1128/jb.74.5.596-604.1957
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIVALENT CATIONS IN THE SPORULATION MEDIUM ON THE THERMAL DEATH RATE OF BACILLUS COAGULANS VAR. THERMOACIDURANS

Abstract: In a previous paper, El-Bisi and Ordal (1956a) reported that increased levels of phosphate, in the growth and sporulation medium, significantly reduced the thermal resistance of spores of Bacillus coagulans var. thermoacidurans. It was postulated that the phosphate anion lessened the availability of divalent cations to the sporulating cells and that spores so produced possessed a reduced thermal resistance. A relationship between the calcium content and the degree of thermal resistance of bacterial spores has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2

Year Published

1962
1962
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 12 publications
2
23
2
Order By: Relevance
“…Youland & Stumbo (1953) found a decimal reduction time at 110" of about 0.3 min (D,,= 0-3). Thermal resistances of the same order were observed by El-Bisi & Ordal (1956a), Amaha, Ordal & Touba (1956), Amaha & Ordal (1957) and others. These and other authors also studied the effect of environmental conditions on the growth, sporulation and heat resistance of B .…”
supporting
confidence: 80%
“…Youland & Stumbo (1953) found a decimal reduction time at 110" of about 0.3 min (D,,= 0-3). Thermal resistances of the same order were observed by El-Bisi & Ordal (1956a), Amaha, Ordal & Touba (1956), Amaha & Ordal (1957) and others. These and other authors also studied the effect of environmental conditions on the growth, sporulation and heat resistance of B .…”
supporting
confidence: 80%
“…It was postulated that higher levels of phosphate interfered with ihe availability of the divalent cations to the sporulating cells. On the other hand, the enrichment of calcium and manganese in the sporulating medium pr'oduced spores of higher calcium and manganese content, and consequently of higher thermoresistantes (Amaha and Ordal, 1957). Slepecky and Foster (1959) also showed that the content of individual metals in spores was flexible within a wide range and was dependent on the relative concentration of the particular metal in the growth medium.…”
Section: Concentrationsmentioning
confidence: 97%
“…Spores with 'maximal manganese or zinc content possessed minimum calcium, and therefore were thermosensitive. Amaha and Ordal (1957) (Perry and Foster, 1955 ;Collier and Murty, 1957 ;Hashimoto et al, 1960;Church and Halvorson, 1959).…”
Section: Concentrationsmentioning
confidence: 99%
“…It has also been reported for other sporeformers (Walker 1964, Bacillus megaterium;Amaha and Ordal 1957, B. coagulans) that as concentrations of phosphate increase, D-values gradually decrease. Amaha and Ordal (1957) suggested that the higher thermal inactivations observed with increased phosphate concentrations in the heating media were related to the removal of certain cations from spores which contributed to the thermal resistance of spores. The loss rate should be greater in the presence of an increased phosphate concentration since it was also assumed that the phosphate effect was that of a chelating agent.…”
Section: Resultsmentioning
confidence: 99%